KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI DAN KEPUASAN KERJA SEBAGAI VARIABEL ANTARA (INTERVENING VARIABLE) - . Ramadhoan (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2015)
The purpose of this study was to examine the effect of indirect picture Work Life Quality of the Employee Performance through Organizational Commitment and Job Satisfaction as an intermediate variable of data collection techniques using the method of observation, documentation methods and questionnaires. Do pre-test to test the quality of data that includes test instrument consisted of test validity and reliability testing, as well as the classic assumption test which is done only data normality test. Data analysis techniques include univariate analysis and confirmatory factor analysis. The results show that there is a direct influence negatively the quality of work life (QWL) on the performance of employees, there is a direct effect of the positive quality of work life (QWL) terhadp organizational commitment and job satisfaction, there is an indirect effect the quality of work life on employee performance through organizational commitment and satisfaction working as an intermediate variable.